Optimizing silicon application to improve growth, grain yield, and nutrient uptake of indica rice (Oryza sativa cv. Bw 367) - Rupasinghe, Geethika; Hanafi, Mohamed Musa; Yusop, Mohd Rafii; Ismail, Roslan; Azizi, Parisa; Liyanage, Mahesh; Mayakaduwa, Amoda Piyangi (Universiti Putra Malaysia, 2022)
The rice plant accumulates silicon (Si) in greater quantity, which varies among the rice genotypes. This study was conducted to determine the optimum fertilization rate and its effect on growth, yield, yield attributes, and soil nutrient uptake. Six different silicon dioxide (SiO2) rates, including 0, 50, 75, 100, 125, and 150 kg SiO2/ha, were applied initially. The optimum rate of SiO2 was obtained by statistical analysis, utilizing the analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) to separate the means. The results showed that shoot dry weight and plant height were significantly affected by Si fertilization. The highest Si tissue concentration of 395.27 μg/100 mg was recorded in 100 kg SiO2/ha treated plants, and their potassium, phosphorous, silicon, and magnesium uptakes were increased by 2, 1.3, 11 and 1.8 folds, respectively. Further, in yield attributes, 32 and 52% increments and a 30% decrease were observed in the total number of grains, filled grains, and unfilled grains per panicle, respectively, and were not significantly different from those observed in 125 kg SiO2/ha rate. The highest grain yield of 104.6 g/pot was obtained with 100 kg SiO2/ha level of Si fertilizer, and it was statistically at par with the yields obtained with 125 kg SiO2/ha. The quadratic function found the rate of Si fertilizer for optimum grain yield (100.5 g/pot) as 115 kg SiO2/ha; thus, it could be concluded that indica rice genotypes need to be fertilized with 115 kg SiO2/ha for optimum yield for higher growth and nutrient uptake.